2020
DOI: 10.24198/sosiohumaniora.v22i3.27259
|View full text |Cite
|
Sign up to set email alerts
|

Cadres of the Integrated Health Post for Elderly and Their Satisfaction: Herzberg Theory Approach

Abstract: Integrated health post (posbindu) is a place for the elderly to obtain various health services to improve their quality of life.  The satisfaction of the health care volunteers (cadres) has an important role in the success of the posbindu. The higher the cadre’s satisfaction, the higher the performance in managing the posbindu. According to Herzberg, two factors that contributed to the work satisfaction, namely motivator factor and hygiene factor. Identifying these factors is important, so that cadres can rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 18 publications
(48 reference statements)
1
10
0
1
Order By: Relevance
“…(2) Recognition: obtaining an appreciation for the accomplishment of the work as a cadre; (3) The work itself: an activity or a task that gives a positive or negative feeling; (4) Possibility for growth: opportunities to develop themselves and improve knowledge/skills/expertise; (6) Responsibilities: the obligation to carry out the work. 10 Moreover, hygiene factors consisted of eight dimensions and 26 categories. 10 The eight dimensions of hygiene factors were: (1) Policies and administration work from the puskesmas and local government: policies or rules and administrative system given by puskesmas and local government to cadres in providing services in the posyandu lansia; (2) Supervision: supervising and guiding the cadre in providing service in the posyandu lansia; (3) Interpersonal relationships: the communication bond between cadres and the supervisors from puskesmas and the local government; (4) Incentives: wages or salaries given to the cadre; (5) Personal life: the condition of the private life of cadres affecting their work as cadres; (6) Working conditions: an environment is affecting cadres in providing services in the posyandu lansia; (7) Status: cadre position in the community; (8) Social relations: help the community, socialize with the community, and make new friends.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…(2) Recognition: obtaining an appreciation for the accomplishment of the work as a cadre; (3) The work itself: an activity or a task that gives a positive or negative feeling; (4) Possibility for growth: opportunities to develop themselves and improve knowledge/skills/expertise; (6) Responsibilities: the obligation to carry out the work. 10 Moreover, hygiene factors consisted of eight dimensions and 26 categories. 10 The eight dimensions of hygiene factors were: (1) Policies and administration work from the puskesmas and local government: policies or rules and administrative system given by puskesmas and local government to cadres in providing services in the posyandu lansia; (2) Supervision: supervising and guiding the cadre in providing service in the posyandu lansia; (3) Interpersonal relationships: the communication bond between cadres and the supervisors from puskesmas and the local government; (4) Incentives: wages or salaries given to the cadre; (5) Personal life: the condition of the private life of cadres affecting their work as cadres; (6) Working conditions: an environment is affecting cadres in providing services in the posyandu lansia; (7) Status: cadre position in the community; (8) Social relations: help the community, socialize with the community, and make new friends.…”
Section: Methodsmentioning
confidence: 99%
“…[12][13][14] Although many items were excluded, the rest of the items were well defined in every dimension. This study revealed that the initial number of dimensions of the motivator and hygiene factors (6 and 8, respectively) that was set based on Herzberg's theory 21 and a study in Bandung city, 10 changed to four dimensions of the motivator factors and nine dimensions of the hygiene factors after employing the principal component analysis and the varimax rotation method with Kaiser normalization.…”
Section: Millions Of Community Health Workers/cadresmentioning
confidence: 99%
See 3 more Smart Citations